2022
DOI: 10.36565/jab.v11i1.389
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Stunting Balita ditinjau dari Aspek Kunjungan Posyandu dan Perilaku Pemberian ASI Eksklusif

Abstract: This research is an analytical survey with a Case Control approach with a ratio of 1: 2. The number of samples was 123 respondents with a quota sampling technique. The collection of data on the incidence of stunting in children under five was obtained from secondary data in Banjarmasin Kuin Raya Public Health Services, while data on maternal age, mother's education level, history of visits to posyandu and history of exclusive breastfeeding were obtained by interview method using a questionnaire. Data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
2
5
0
2
Order By: Relevance
“…The results of this study analysis showed that the most common indicators of Behavior of Nutrition-aware Families were still lack of nutritional supplements, namely Fe tablets and vitamin A (71.1%), regular weight weighing (67.2%), and exclusive breastfeeding for up to 6 months (56.5%). This study is in line with previous research that the incidence of stunting correlates with exclusive breastfeeding for up to 6 months (Lindawati et al, 2023;Hadi et al, 2022), visits to integrated health posts with child weighing (Prasetyani et al, 2023), and supplementation of Fe and vitamin A (Silaban et al, 2022).…”
Section: Behavior Of Nutrition-aware Families and The Incidence Of St...supporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study analysis showed that the most common indicators of Behavior of Nutrition-aware Families were still lack of nutritional supplements, namely Fe tablets and vitamin A (71.1%), regular weight weighing (67.2%), and exclusive breastfeeding for up to 6 months (56.5%). This study is in line with previous research that the incidence of stunting correlates with exclusive breastfeeding for up to 6 months (Lindawati et al, 2023;Hadi et al, 2022), visits to integrated health posts with child weighing (Prasetyani et al, 2023), and supplementation of Fe and vitamin A (Silaban et al, 2022).…”
Section: Behavior Of Nutrition-aware Families and The Incidence Of St...supporting
confidence: 92%
“…Meanwhile, the last phase of 9-12 months of breastfeeding contains many amino acids for protein needs that function for optimal muscle growth. Thus, the growth of exclusively breastfed babies is optimal and can prevent stunting (Lindawati et al, 2023;Hadi et al, 2022).…”
Section: Behavior Of Nutrition-aware Families and The Incidence Of St...mentioning
confidence: 99%
See 3 more Smart Citations